Large Cell Calcifying Sertoli Cell Tumor with Macrocalcification in a Partially Resected Testis - Mahmoud Bardisi; Mohamad Nidal Khabaz; Jaudah Ahmad Al-Maghrabi (Hindawi Limited, 2020)
Large cell calcifying Sertoli cell tumors (LCCSCTs) are extremely rare, with less than 100 tumors being described to date. Most of the tumors are benign with a few malignant cases, and aggressive behavior is infrequent. These tumors are a type of Sertoli cell tumor, and these tumors comprise less than 0.3% of all testis tumors in Saudi Arabia. They usually occur in boys and young adults and can affect one or both testicles in multifocal form causing microcalcifications. A 28-year-old male visited our hospital with left testis pain. Physical examination of the scrotum revealed that both testicles were normal sized with no palpable mass. Ultrasonography evaluation revealed grade 3 left varicocele and an incidental 9 mm calcified mass in the right testicle, which was further confirmed by MRI. Partial orchiectomy was performed. Clinical data, radiological studies, and morphological and immunohistochemical characteristics were analyzed.